A study on ITS-90 type 3 non-uniqueness between freezing points of Al and Ag. (July 2016) - Coppa, Graziano; Merlone, Andrea
Highlights: An investigation about type 3 non-uniqueness at high temperatures is presented. The temperature amplifier device was employed due to its stability and reliability. Non-uniqueness differences less than 10 mK were found. HTSPRTs under test proved to be not stable enough at very high temperatures. Abstract: This work presents an investigation about the type 3 non-uniqueness of the International Temperature Scale of 1990 (ITS-90) between the aluminium (660 °C) and silver (962 °C) freezing points, carried out at the Italian National Institute of Metrology (INRiM) within the framework of the EMRP—JRP SIB10 NOTED (Novel Techniques for Traceable Temperature Dissemination). For this purpose six High Temperature Standard Platinum Resistance Thermometers (HTSPRTs) from different manufacturers were calibrated at the ITS-90 fixed points, then intercompared in a sodium Gas Controlled Heat Pipe (GCHP) at 25 K intervals between the aforementioned fixed points; a temperature uniformity and stability within ±0.5 mK was achieved in the whole range between 660 °C and 962 °C. This paper presents the results of type 3 non-uniqueness analysis of these test HTSPRTs, together with problems deriving from their stability, which is the largest source of uncertainty in this work.